PENGARUH KEPEMILIKAN ULTIMAT TERHADAP KEINFORMATIFAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Susilowati, Isabella Henny; Sanjaya, IPutu Sugiartha (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2015)
Ultimate ownership is ownership directly and indirectly in public companies to identify the ultimate owners of public Vendor. Ultimate owner has the right greater control of cash fow rights is called the controlling shareholder. This causes problems between controlling shareholders and non-controlling shareholders, which will afect earnings informativeness. Informativeness proft is profit information that could afect stock returns. This study uses the 149 companies listed on the Stock Exchange in 2004-2009. Te data used in this study is proft and equity in the annual fnancial statements, as well as the ownership of the company. Tis test uses regression analysis moderasian with moderating variable Cash Flow Right Leverage (CFRL). CFRL is the diference between control rights to cash fow rights. The results of this study showed that the diference of control rights to cash fow rights owned by the controlling shareholders make a proft informativeness be low because shareholders can infuence policy to make accounting information, thus making proft informativeness be low.Keywords: ultimate ownership, control rights, cash fow rights, earnings informativeness.